Small Sets of Novel Words Are Fully Retained After 1-Week in Typically Developing Children and Down Syndrome: A Fast Mapping Study. (30th October 2018) - Sakhon, Stella; Edwards, Kelly; Luongo, Alison; Murphy, Melanie; Edgin, Jamie
Abstract: Objectives: Down syndrome (DS) is a population with known hippocampal impairment, with studies showing that individuals with DS display difficulties in spatial navigation and remembering arbitrary bindings. Recent research has also demonstrated the importance of the hippocampus for novel word-learning. Based on these data, we aimed to determine whether individuals with DS show deficits in learning new labels and if they may benefit from encoding conditions thought to be less reliant on hippocampal function (i.e., through fast mapping).Methods: In the current study, we examined immediate, 5-min, and 1-week delayed word-learning across two learning conditions (e.g., explicit encoding vs . fast mapping). These conditions were examined across groups (twenty-six 3- to 5-year-old typically developing children and twenty-six 11- to 28-year-old individuals with DS with comparable verbal and nonverbal scores on the Kaufman Brief Intelligence Test – second edition) and in reference to sleep quality.Results: Both individuals with and without DS showed retention after a 1-week delay, and the current study found no benefit of the fast mapping condition in either group contrary to our expectations. Eye tracking data showed that preferential eye movements to target words were not present immediately but emerged after 1-week in both groups. Furthermore, sleep measures collected via actigraphy did not relate to retention in either group.Conclusions: This study presents novel data on long-term knowledge retention in reference to sleep patterns in DS and adds to a body of knowledge helping us to understand the processes of word-learning in typical and atypically developing populations. ( JINS, 2018, 24, 955–965)